State power in blue. (March 2016) - Coleman, Mat
Abstract: In this article I explore how geographers might go about studying the everyday contexts of police power, given specifically the emphasis today in political geography on the practice of state power. Rather than endorse police practice as a relatively accessible and straightforward realm for researchers, I emphasize instead the uneventful and sometimes disappearing aspects of police work which makes it hard to excavate and interrogate, especially for non-police. Reflecting on various fieldwork experiences, I argue that the basic methodological tools that geographers have at their disposal to bring down the 'blue wall' of police practices can do the opposite: produce a tentative mode of knowledge which grasps, qualitatively and quantitatively, at the problem of the social and force relations of policing. I conclude that rather than a fix to the cruddiness of police power, accepted qualitative and quantitative methodologies constitute the 'blue wall' of police practice.